RESILIENCE OF NARCOTICS INMATES IN SERVING THEIR SENTENCE IN CLASS IIB DETENTION CENTRE IN PANDEGLANG - Pratiwi, Ayu Inka; Equatora, Muhammad Ali; Muhammad, Ali (ANAYASA : Journal of Legal Studies, 2024)
The purpose of this study is to determine the factors that form the resilience of narcotics prisoners and how the process of prisoners becoming resilient individuals. The method used in this research is qualitative method using case studies. Data collection is carried out using in-depth interview methods, participant observation, and documentation. Data analysis techniques use triangulation. This study shows that seven factors can affect resilience, namely: emotional regulation, immune control, optimism, casual analysis, empathy, self-efficacy, and reaching out. The process that prisoners go through is not easy, but the three informants deal with problems in their own way.